Effectiveness of Bacillus thuringiensis Berliner var. kurstaki on the grape berry moth Lobesia botrana Den. and Shiff. (Lepidoptera, Tortricidae) under field and laboratory conditions in Crete - Roditakis Ν.Ε. (ENTOMOLOGIA HELLENICA, 1986)
The effectiveness of Bacillus thuringiensis Berliner var. kurstaki (Dipel Abbot Lab.) against the grape berry moth (Lobesia botrana Den. & Shiff.) was evaluated under laboratory and field conditions. Under laboratory conditions (24±0.5°C, 55±5% r.h., 2,000 Lux, and 16 hours light daily) B. thuringiensis was compared to triflumuron and methomyl on egg hatching and shallow entries per grape berry. B. thuringiensis had no effect on egg hatching while methomyl and triflumuron had ovicidal action. Shallow entries per grape berry were 0.9-1, 0, 0 and 4.55 for B. thuringiensis, triflumuron, methomyl and control, respectively. Under field conditions, using as criteria for the timing of sprays: a. pheromone and food trap catches and b. visual counting of egg laying and a threshold of 20-30 eggs/100 grapes, two applications of B. thuringiensis at Kastelli Pediados in 1981 and four at Peza in 1982 were made both at the 2nd and 3rd flights. Its effectiveness was 96-100% and 92% at Kastelli Pediados and 73-75% at Peza.